Microplastics-Induced Eryptosis and Poikilocytosis in Early-Juvenile Nile Tilapia (Oreochromis niloticus) - Hamed, Mohamed; Osman, Alaa G. M.; Badrey, Ahmed E. A.; Soliman, Hamdy A. M.; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2021)
This study aims to assess the impact of microplastics (MPs) on erythrocytes using eryptosis (apoptosis) and an erythron profile (poikilocytosis and nuclear abnormalities), considered to be novel biomarkers in Nile tilapia (Oreochromis niloticus). In this study, four groups of fish were used: The first was the control group. In the second group, 1 mg/L of MPs was introduced to the samples. The third group was exposed to 10 mg/L of MPs. Finally, the fourth group was exposed to 100 mg/L of MPs for 15 days, following 15 days of recovery. The fish treated with MPs experienced an immense rise in the eryptosis percentage, poikilocytosis, and nuclear abnormalities of red blood cells (RBCs) compared with the control group in a concentration-dependent manner. Poikilocytosis of MP-exposed groups included sickle cell shape, schistocyte, elliptocyte, acanthocyte, and other shapes. Nuclear abnormalities of the MPs-exposed groups included micronuclei, binucleated erythrocytes, notched, lobed, blebbed, and hemolyzed nuclei. After the recovery period, a greater percentage of eryptosis, poikilocytotic cells, and nuclear abnormalities in RBCs were still evident in the groups exposed to MPs when crosschecked with the control group. The results show concerning facts regarding the toxicity of MPs in tilapia.